Prospective Analysis and Innovative Path Research on Silver Sports Economy in the Context of Aging Society - Zhang, Aihua (Journal of Ecohumanism, 2024)
This study focuses on the prospects and innovative pathways for the development of the silver-haired sports economy in the context of an ageing society. The proportion of the global population over 65 years old is expected to increase from 9% in 2019 to 16% in 2050, highlighting the huge potential of the silver-hair economy. This paper adopts a mixed research methodology, combining spatial econometric modelling and rootedness theory, to explore in depth the current development status, trend forecasts and innovation paths of the silver-haired sports economy. The study constructs a silver-hair sports economy assessment system containing 22 indicators, and uses panel data to analyse the development level of 31 provinces, municipalities and autonomous regions in China from 2010 to 2023, and the results show that the average annual growth rate of silver-hair sports economy reaches 15.7%, but the gap between Beijing, Tianjin, Shanghai and Guangdong and the central and western regions reaches 1.8 times. Analyses based on the Spatial Durbin Model show that every 1 percentage point increase in silver-haired sports consumption can drive 0.3 percentage points of GDP growth in neighbouring regions. Through a Delphi method research of 150 industry experts, it is predicted that the size of China's silver-haired sports market will exceed RMB 3 trillion in 2030, increasing its share of GDP to 2%. The qualitative study reveals three innovative paths: intelligent transformation, ecosystem construction, and cross-border integration, and proposes specific strategies such as "integration of sports and medicine" and "social platform for silver sports". The results of the study provide data support and theoretical basis for the formulation of policies for the development of the silver sports economy, and provide important insights into the industrial transformation of an aging society.